Quantifying upper extremity performance with and without assistance of a soft-robotic glove in elderly patients: A kinematic analysis - Anne van Ommeren; Bob Radder; Anke Kottink; Jaap Buurke; Gerdienke Prange-Lasonder; Johan Rietman (Medical Journals Sweden, 2019)
Objective: To explore the direct influence of a soft-robotic glove on movement duration and movement execution in elderly people with decreased hand function during a reach-and-grasp task. Design: Cross-sectional study. Patients: Eight subjects, aged 55+ years, with decreased hand function. Methods: The direct effect of the glove was explored using kinematic analysis during a reach-and-grasp task with a light (100 g) and heavy (1,000/2,500 g) cylindrical object, performed with and without the soft-robotic glove. Results: There was no difference in total movement time between performance with and without the glove. With the glove, the relative time needed to transport the heavy object was shorter, while the relative time needed to grasp the heavy object was longer. In addition, transporting light objects involved a lower peak velocity and larger elbow extension, and grasping the object involved a larger hand opening compared with without glove. Conclusion: As expected, no positive influence of the soft-robotic glove was found on total movement duration in elderly subjects. The influence of the glove on movement execution varied with movement phase. The positive and negative effects found may be due to a perceived confidence while carrying heavy objects with the glove, or compensation for loss of sensation, respectively. This information can be used to improve the glove design.